Arsitektur Supramolekul ; Rahasia Gebrakan Piranti Canggih Fotonok, Elektronik, Lonik Ultramutakhir - HARTOMO, Anton J. (Andi Offset, 1995)
Arsitektur Supramolekul ; Rahasia Gebrakan Piranti Canggih Fotonok, Elektronik, Lonik Ultramutakhir